2015
DOI: 10.1007/s12192-014-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of geldanamycin-activated P70S6K and Hsp70 against beta-amyloid-induced hippocampal apoptosis: an approach to long-term memory and learning

Abstract: One of the neuropathological hallmarks of Alzheimer's disease (AD) is the accumulation of betaamyloid peptides (Aβ) in senile plaques. Aβ-induced oxidative stress is believed to be responsible for degeneration and apoptosis of neurons and consequent cognitive and memory deficits. Here, we investigated the possible neuroprotective effect of the heat shock protein 90 (Hsp90) inhibitor geldanamycin (GA) against amyloid pathogenesis in adult male Wistar rats. GA or vehicle was injected into the lateral cerebral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…Here, we show that a single intrahippocampal application of A β induces an impairment of memory, but not of learning, as well as increased burrowing and freezing behaviors without affecting locomotion or hippocampal integrity. Our result that A β affects contextual memory is consistent with the overwhelming evidence that intracerebroventricular or intrahippocampal application of A β induces a deficit in retention of the inhibitory avoidance task [ 6 13 , 39 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we show that a single intrahippocampal application of A β induces an impairment of memory, but not of learning, as well as increased burrowing and freezing behaviors without affecting locomotion or hippocampal integrity. Our result that A β affects contextual memory is consistent with the overwhelming evidence that intracerebroventricular or intrahippocampal application of A β induces a deficit in retention of the inhibitory avoidance task [ 6 13 , 39 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Alzheimer's disease (AD) is a disorder characterized by severe cognitive impairments [ 1 3 ] and by the presence of senile plaques that contain the amyloid beta peptide (A β ) [ 3 5 ]. A strong correlation between the levels of soluble oligomeric forms of A β and the cognitive decline in AD patients [ 3 5 ] has been further supported by the findings that intracerebral infusion of A β , particularly into the hippocampus, disrupts learning and memory in rodents [ 6 13 ].…”
Section: Introductionmentioning
confidence: 98%
“…Animal models and post-mortal studies in subjects who suffered from posttraumatic disorder suggested that increase in the hippocampal pro-apoptotic factors could induce anxiety (Khalifeh et al (2015) have demonstrated that Bcl2 level, a main antiapoptotic factor, is related to anxiety behavior; likewise, data from transgenic mice for Bcl2 (Bcl2 knockout) showed that they had more anxiety-like behavior compared to the wild type (Einat et al 2005). In line with these results in our previous work, we showed that GA pretreatment increased the Bcl2 level in Aβ-injected rats (Zare et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Aβ 1-42 (Sigma-Aldrich, St. Louis, MO, USA) was dissolved in phosphate buffer saline (PBS, 0.1 M) at a concentration of 200 ng/μl and incubated at 37°C for 5 days to form fibrils; then, the solution was further diluted with PBS to a final concentration of 10 ng/μl (Zare et al 2015). Microtubuleassociated protein light chain 3 (LC3), autophagy-related protein 7 (Atg7), Atg12, and β-actin antibodies were acquired from Cell Signaling Technology (Beverly, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…61) Caspase 3 is involved in the cleavage of amyloid-beta precursor protein (APP), which is associated with neuronal death in AD. 62) Targeted inhibition of Caspase-3 by Ost may attenuate Aβ-induced apoptosis, 63,64) and may be a new therapeutic for preventing neuronal apoptosis and inhibiting progression of AD.…”
Section: Discussionmentioning
confidence: 99%